ANALISIS KINERJA SIMPANG BERSINYAL PADA SIMPANG EMPAT KETANDAN DAN SIMPANG EMPAT SANGKRAH KOTA SURAKARTA DENGAN PERANGKAT LUNAK PTV VISTRO - Budi Yulianto; Uti Najwa Atras; Setiono Setiono (Matriks Teknik Sipil, 2024)
The city of Surakarta, located in the southern part of java island, is one of the cities that has become a trading node in the golden triangle area in the province of Central Java. This caused traffic jams at several points in Surakarta City such as the Simpang Empat Ketandan and Simpang Empat Sangkrah. Traffic analysis is needed to reduce the conflict problems that occur. PTV Vistro is a software used to analyze the performance of signalized intersections using the HCM 2010 method based on the degree of saturation (DS) and delay (D). Statistical Product and Service Solutions (SPSS) is used to validate base scenario modeling with the queue length parameter (m) to produce data that is representative of conditions in the field. The analysis was carried out under existing conditions and a single scenario. The results of the analysis at the two intersections produce a single scenario with the optimization type Minimize Critical Movement (Split & Cycle Time) having the best performance compared to other optimizations. Simpang Empat Ketandan during the morning rush hour produces DS = 0.36 and D = 36 sec/pcu and during the afternoon rush hour the values DS = 0.48 and D = 42 sec/pcu. The Simpangrah Empat intersection during the morning rush hour resulted in a value of DS = 0.24 and D = 14 sec/pcu and during the afternoon rush hour the value of DS = 0.45 and D = 18 sec/pcu.